Increase in Blood Levels of Growth Factors Involved in the Neuroplasticity Process by Using an Extremely Low Frequency Electromagnetic Field in Post-stroke Patients - Cichoń, Natalia; Bijak, Michał; Czarny, Piotr; Miller, Elżbieta; Synowiec, Ewelina; Sliwinski, Tomasz; Saluk-Bijak, Joanna (Frontiers in Aging Neuroscience, 2018)
Background: Neuroplasticity ensures the improvement of functional status in patients after stroke. The aim of this study was to evaluate the effect of extremely low frequency electromagnetic field therapy (ELF-EMF) on brain plasticity in the rehabilitation of patients after stroke. Methods: 48 patients were divided into two groups. In the study group, the patients additionally underwent ELF-EMF therapy. In order to determine the level of neuroplasticity, we measured the plasma level of the brain-derived neurotrophic factor, the vascular-endothelial growth factor, as well as brain-derived neurotrophic factor (BDNF) mRNA expression. Additionally, we determined the molecule levels for hepatocyte growth factor, stem cell factor, stromal cell-derived factor 1α, nerve growth factor β, and leukaemia inhibitory factor, using 5plex cytokine panel in plasma. We assessed functional recovery using Barthel Index, Mini-Mental State Examination, Geriatric Depression Scale, National Institutes of Health Stroke Scale, and modified Rankin Scale. Results: We observed that ELF-EMF significantly increased growth factors and cytokine levels involved in neuroplasticity, as well as promoted an enhancement of functional recovery in post-stroke patients. Additionally, we presented evidence that these effects could be related to enhancement of gene expression on the mRNA level. Moreover, a change of BDNF plasma level was positively correlated with Barthel Index, MMSE, and negatively correlated with GDS. Conclusion: Extremely Low Frequency Electromagnetic Field therapy improves effectiveness of rehabilitation of post-stroke patients by improving neuroplasticity processes.